Characterising integrated content-language pedagogies of global perspectives teachers in Dutch bilingual schools - van Kampen, Evelyn; Meirink, Jacobiene; Admiraal, Wilfried; Berry, Amanda (Language, culture, and curriculum, 2021)
This study aims to characterise teachers' integrated content-language learning pedagogies teaching the skills-focused subject Global Perspectives (GP) in Dutch bilingual upper-secondary-schools. Eleven teachers from seven bilingual schools across the Netherlands participated in the study in the school-year 2016-2017. To obtain insight into teachers' pedagogies, semi-structured interviews and observations of GP lessons were used. Dalton Puffer's Cognitive Discourse Functions (CDF) construct [(2013). A construct of cognitive discourse functions for conceptualizing content-language integration in CLIL and multilingual education. European Journal of Applied Linguistics, 1(2), 216-253. https://doi.org/10.1515/eujal-2013-0011], in combination with a focus on subject-specific Culture, was used as a heuristic to analyse the integrated content-language pedagogies of teachers. Main findings include that the participating schools had three distinct Intended Curriculum foci and, within these, five different types of integrated content-language learning pedagogies were identified. Main implications discussed are that focusing on subject-specific culture and using the CDF Construct is a useful heuristic to allow analysis of teachers' integrated content-language pedagogies, and that it may also provide a useful framework for both pre- and in-service teachers in CLIL contexts to emphasise the integrated nature of CLIL teaching.